Parental involvement in helping child succeed in schools in Sri Aman, Sarawak / Abang Suhaili Abang Akim - Abang Akim, Abang Suhaili (2012)
A study on parental involvement in helping child succeed in school in Sri Aman, Sarawak involves six primary schools in Sri Aman District. It was conducted to determine the relationship of parental involvement in helping child succeed in the UPSR public examination. To determine the level of parental involvement of selfefficacy, parent- focused invitation, empowerment-focused invitation, child focused invitation, school-focused invitation, parent responsibilities-focused, and communication-focused, questionnaire administered to 120 parents. Based on Hoover-Dempsey & Sandler model (2005) the findings revealed that parental involvement has great influenced on child succeed in the UPSR. The highest level of parent’s involvement on Parent’s Self-Efficacy is their efforts to help my child learn are successful (M=4.70; SD=0.806); the highest level of parent’s involvement on School-Focused Invitation is '’“'When my child first enrolled in this school, we were much welcomed' (M=4.97; SD=0.733). It is also found that the highest level of parent’s involvement on empowerment-focused invitations is on “this school does a good job o f letting me know about ways I can help out in sch o o l (M=4.93; SD=0.650). The highest level of parent’s involvement on Communication-Focused Invitation is on “This school does a good job o f letting me know about the school rules and policies’ (M=4.73; SD=0.809). In term of parent’s responsibility towards child succeeds, “Communicate with my child’s teacher regularly" gives the highest mean (M=4.95; SD=858) . Although no correlation between Parent-Efficacy and UPSR result, there is a positive correlation between Child-focused and UPSR result, which was statistically significant (r, = .184, P — .044). The findings on parental involvement in children’s education are very much associated with a range of enhance student outcomes including academic achievement and motivation for schoolwork and in line with the learning theories in helping child succeed in schools.